Three‐Dimensional Silver Nanoparticle Formation Using Femtosecond Laser Irradiation in Phosphate Glasses: Analogy with Photography. (24th July 2014) - Marquestaut, N.; Petit, Y.; Royon, A.; Mounaix, P.; Cardinal, T.; Canioni, L.
<x xml:space="preserve">Abstract</x> Three‐dimensional patterning of metal–dielectric composites is achieved at the sub‐micrometer scale in glass. A high silver‐content zinc‐phosphate optical transparent glass is structured by means of a near‐infrared femtosecond laser via non‐linear absorption processes. The silver ions embedded in glass photochemically react under controlled laser irradiation, inducing ion clustering and the formation of nucleation centers. A subsequent thermal development causes silver reduction and growth into metallic nanoparticles. A very strong surface plasmon resonance is measured, revealing the very high concentration of metallic particles. The direct laser writing process enables inscriptions of silver nanoparticle domains well below the diffraction limit (∼100 nm). A very detailed parametric study is given, leading to the first thorough understanding of the ultrafast laser‐induced photochemistry in silver‐containing glass materials. These nanostructures are considered promising candidates for the design of highly efficient sensing devices via plasmonics and, beyond that, for photonics and metamaterials applications.